From gender equality to gender justice: the Egyptian revolution and public sphere debates - El Azzazy, Heba Moahmed (AUC Knowledge Fountain, 2013)
Living in an era of a global gender agenda in which concepts and frameworks travel across the world presents many challenges when it comes to discussions of women’s rights in Egypt. In the decade preceding the January 25, 2011 revolution, significant progress was made regarding Egyptian women’s legal rights, especially in the domain of family law reform. Hence expectations were high that Egyptian women’s rights would advance following the Jan 25, 2011 revolution. Unfortunately with the transformations of the political landscape suggested otherwise. During the rule of the Muslim Brotherhood between 2011 to June 2013, several women’s rights legislations were revisited and several attempts and concrete steps were taken to repeal certain family laws that had been regarded as gains for Egyptian women. This thesis explores the different strategies, tactics and engagement that women’s rights advocates adopted during this period. While the global conception of gender equality was one of the main frameworks adopted in Egypt to promote women’s rights prior to the revolution, in this thesis, I explore the tensions between women’s rights legal activists and the Muslim Brotherhood regarding conceptions of gender equality and gender justice.